Metastasis to orbit: A case series from tertiary eye center in Western India - Bhanvadia, Viral M; Kathiara, Ravija; Shah, Ami M; Devanhalli, Swati (Indian Journal of Case Reports, 2024)
This study aims to understand the pattern of the metastatic tumors to orbit in a tertiary eye center. Metastasis to orbit is extremely rare and challenging to diagnose and often mimics with primary orbital tumor. Due to the tremendous recent advances in cancer therapy, surveillance, ancillary histopathology, and imaging techniques for primary tumor diagnosis, the longevity of patients increases, leading to more chances of detection of orbital metastasis. We retrospectively studied and reviewed a case series of five patients with orbital metastasis from various systemic malignancies from 2018 to 2023. Out of five patients, three patients were from metastasis from breast carcinoma, one from neuroblastoma, and monophasic synovial sarcoma each, found a median age of 49 years (range=3–70 years). The most common symptoms and sign were painful proptosis and restriction of ocular motility, respectively.